Samiskt skogsutnyttjande, dimensionsavverkningar och naturvärden - Wikström, Henrik (2004)
In order to understand the human impact on today's remaining "virgin" forest and to develop sensible management strategies for future reserves, it is necessary to know how these forests have developed. This knowledge can be gained by using forest history analysis. here are large areas of forests still untouched by modern forestry in the mountainous region in the county of Norrbotten. These forests are highly interesting study objects from an ecological and historical point of view. My study was carried out in a peripherally located mountainous area. The study area has for a shorter period been subjected to forest exploitation but has for a long time been habited by Sámi people. The aim of this study was to interpret how human activities have influenced the development and the present state of the forest. The present ecological values were put in relation to the result. Forest survey data from the first (1910) forest survey and present data records were compared to interpret the development of the forest. In my study I have shown that the study area was not commercially logged until 1901. Before that, the study area was for a long time mainly influenced by extensive Sámi forest use. Settlers influenced the area to a small extent and mainly during the 19th century. The commercial logging, e.g., high grading had a much more dramatic impact on the forest compared to preindustrial forest use. The high grading has to a certain degree had a negative influence on present ecological and cultural values at a stand level. Although relatively large amounts of timber were logged, no transformation has occurred on a landscape level. The last 90 years without forestry, with a de-escalation in other forest use and effective fire suppression has led to a drastic increase in the standing timber volume and the forest has to a certain degree "recovered". Natural processes, except the absence of fire, have to a higher extent been the prevailing conditions for the forest development. Today the forest has a relatively large supply of valuable substrates and structures and there occurs at least twenty or so red listed species. Traces of preindustrial forest use are rare in the present day forests and should hence, like the red listed species, be protected. They also make the area interesting as an object for forest history research and give an extra dimension to people's enjoyment of the forest.